Correlation Between CT Features of Active Tuberculosis and Residual Metabolic Activity on End-of-Treatment FDG PET/CT in Patients Treated for Pulmonary Tuberculosis - Lawal, Ismaheel O.; Mokoala, Kgomotso M. G.; Mathebula, Matsontso; Moagi, Ingrid; Popoola, Gbenga O.; Moeketsi, Nontando; Nchabeleng, Maphoshane; Hikuam, Chris; Ellner, Jerrold J.; Hatherill, Mark; Fourie, Bernard P.; Sathekge, Mike M. (Frontiers in Medicine, 2022)
Background: Patients who complete a standard course of anti-tuberculous treatment (ATT) for pulmonary tuberculosis and are declared cured according to the current standard of care commonly have residual metabolic activity (RMA) in their lungs on fluorine-18 fluorodeoxyglucose positron emission tomography/ computed tomography(FDG PET/CT) imaging. RMA seen in this setting has been shown to be associated with relapse of tuberculosis. The routine clinical use of FDG PET/CT imaging for treatment response assessment in tuberculosis is hindered by cost and availability. CT is a more readily available imaging modality. We sought to determine the association between CT features suggestive of active tuberculosis and RMA on FDG PET/CT obtained in patients who completed a standard course of ATT for pulmonary tuberculosis. Methods: We prospectively recruited patients who completed a standard course of ATT and were declared cured based on negative sputum culture. All patients had FDG PET/CT within two weeks of completing ATT. We determined the presence of RMA on FDG PET images. Among the various lung changes seen on CT, we considered the presence of lung nodule, consolidation, micronodules in tree-in-bud pattern, FDG-avid chest nodes, and pleural effusion as suggestive of active tuberculosis. We determined the association between the presence of RMA on FDG PET and the CT features of active tuberculosis. Results: We enrolled 75 patients with a mean age of 36.09 ± 10.49 years. Forty-one patients (54.67%) had RMA on their FDG PET/CT while 34 patients (45.33%) achieved complete metabolic response to ATT. There was a significant association between four of the five CT features of active disease (lung nodule, Odds ratio [OR]=10.40, 95% confidence interval [CI]=3.04-35.67, p<0.001; consolidation, OR=9.28, 95% CI=1.11-77.5, p=0.018; micronodules in tree-in-bud pattern, OR=30.86, 95% CI=6.34-147.97, p=0.040; chest nodes, OR=3.48, 95% CI=1.01-11.95, p=0.040). Pleural effusion (seen in two patients) was the only CT feature of active disease without a significant association with the presence of RMA. Conclusion: CT features of active tuberculous disease have significant associations with the presence of RMA on EOT FDG PET. This suggest that findings on CT may be used in lieu of FDG PET/CT for treatment response assessment of pulmonary tuberculosis.